Peningkatan Kemampuan Membaca Permulaan Melalui Media Kartu Huruf pada Kelompok A di Taman Kanak-Kanak Santa Theresia 1 Pangkalpinang - Imelda Indah Bulan (Jurnal Pendidikan Tuntas, 2023)
This classroom action research aims to improve beginning reading skills in group A through letter cards at St. Kindergarten. Theresia 1 Pangkalpinang. The method used in this research is collaborative classroom action research using the Kemmis and Mc Taggart model. PTK is implemented as an effort to overcome problems that arise in the classroom. This method is carried out in three stages, namely planning, implementation and reflection. The research subjects were students from Group A of St. Theresia 1 Pangkalpinang, totaling 15 children. The object of this research is the beginning reading ability in group A. The data collection method used is observation. Technical data analysis was carried out descriptively qualitatively and quantitatively. The success indicator set is a minimum of 75% of 15 children who have achieved initial reading skills. This research was conducted in two cycles. The results of research on the development of early reading abilities using letter card media in general for the categories of children who are developing well and children who are developing very well, in quantity there was an increase where at the beginning of the study there was only 1 child, but at the end of the study there were 11 children (6 children included good category and 5 children in the very good category) which means that the Classroom Action Research was considered successful in meeting the minimum target. Thus, it can be concluded that activities to improve initial reading skills using letter cards in Group A Kindergarten St. Theresia 1 Pangkalpinang has had a positive impact as indicated by an increase in the quantity of children who are able to read at the beginning by using letter cards properly and correctly. Keywords: beginning reading ability, letter card media, early childhood